Ethnic sorting in the Netherlands - Aslan Zorlu; Jan Latten (Institute for the Study of Labor (IZA), 2007)
This paper examines the residential mobility behaviour of migrants and natives in the Netherlands using a rich administrative individual data file. The inclination to move and the choice of destination neighbourhood are estimated, correcting for the selection bias of movers. Subsequently, the role of preferences in the mobility behaviour is implicitly derived from regression estimates. The analysis shows that the percentage of natives in the destination neighbourhood is predicted to be about 18 percentage points lower for non-western migrants than for natives. About 65 percent of the differential is explained by their observable characteristics; the remaining part can largely be attributed to preferences and discrimination. No indication is found of the spatial assimilation of second-generation non-western migrants. On the other hand, the mobility pattern of the second-generation western migrants is similar to that of natives.
Keywords: J1; 330; Migrants; residential segregation; Migranten; Wohnstandort; Wohnungswechsel; Ethnische Gruppe; Niederlande